Relationship between width and length ratios of upper anterior teeth in young Chilean population. - Jorge Troncoso-Pazos; Constanza Courdurier; Christian Santi; Pedro Christian Aravena (Universidad de Concepción., 2017)
Introduction: Knowledge about the size and proportion of upper anterior teeth allows dental rehabilitation taking into consideration the local parameters of a population. The aim of this research is to determine the width, length and the relationship between width and length of central incisor, lateral incisor and canine teeth in both sexes in young Chilean population. Methodology: A cross-sectional study was performed. Study subjects included 187 dentistry students from two Chilean cities (mean age 21.35±2.7 years, 52.9% men). The teeth width and height were measured and the width/height ratio was calculated. Differences in measurements according to sex was analyzed (p<0.05; STATA v.10.0). Results: The width and height of the teeth were statistically and proportionally larger in men (p<0.05). The width/height ratio of lateral and canine incisors was significantly higher in women (p<0.05). Conclusion: In a sample of young Chileans, upper anterior teeth were longer and wider in men. However, the width/height ratio of teeth was found to be significantly higher in women.